Applicability of the Motivation Theories of Maslow, Herzberg and Vroom to Contemporary Business Organizations in Oman - AlAmrani, Khadeem A. (International Journal of Economics, Business and Management Studies, 2020)
This paper examines the applicability of the motivation theories of Maslow, Herzberg and Vroom to contemporary business organizations in Oman, taking Sohar Industrial Area as a context. The data for the study was collected through a structured questionnaire involving 50 respondents. Descriptive analysis and nonparametric test of Chi-square have been used to identify the motiving factors and their relevance to the motivational theories. The study found that financial incentives, training, promotion, work flexibility, cooperation of employees, work supervision, office and field environment were the most motivating factors. Results of the study confirmed that theories of Maslow, Herzberg, and Vroom provide a basis for exposing and understanding the motivational factors in the Omani labour force context.